KEANEKARAGAMAN JENIS POHON SEBAGAI SALAH SATU INDIKATOR KESEHATAN HUTAN LINDUNG (Studi Kasus di Kawasan Hutan Lindung yang Dikelola oleh HKm Beringin Jaya) - Rahmat Safei; Hari Kaskoyo; Arief Darmawan; Fansuri Fikri Haikal (Jurnal Belantara, 2021)
Protection forest becomes a forest area with the main function as protection of life support systems. The health condition of protected forests has a great influence on the environment of the ecosystem. It is important to assess the health of protected forests in view of their main function. Thus to determine the health condition of the forest, one indicator that can be used is tree biodiversity. Biodiversity is the richness of life found on earth. Assessment of biodiversity indicators is very necessary to do because it is sensitive to changes, ecological system indicators, spatial heterogeneity, temporal, and and the order in the food chain. This study aims to determine the diversity of tree species in protected forest areas managed by HKm Beringin Jaya as an indicator of forest health assessment. The study was conducted using the Forest Health Monitoring (FHM) method. The results showed that the final value of forest health status with indicators of biodiversity (tree species diversity) in the protected forest area managed by HKm Beringin Jaya was in the good category of 50% in cluster plots (2, 5 and 6) and bad by 50% on cluster plots (1, 3 and 4), thus showing that the protected forest area managed by HKm Beringin Jaya has a fairly healthy (stable) condition with a moderate category.